Mapping spatio-temporal patterns of creative industries development in the Czech Republic - Pavel Bednář; Lukáš Danko (Časopis Socìalʹno-Ekonomìčnoï Geografìï, 2018)
Creative industries characterized by subsectors of architecture, design, and advertising represent an important segment in im-plementation of post-Fordist economy principles. Hence, the governments and scholars are devoted to quantitative mapping of crea-tive industries. The results of this mapping provide insight into number, structure and spatial distribution in a given area for subse-quent identification of smart specialization of cities and regions. Furthermore, they serve as a basis for strategic planning of regional innovation systems. Finally yet importantly, this mapping is the basis for following qualitative mapping through research methods such as focus groups and the Delphi method among key actors of the particular creative ecosystem. Unique feature of this paper is mainly in the methodology, which is detached from the traditional static view on the quantita-tive mapping of creative industries dealing with cross-sectional data solely. Therefore, this paper develops their use to spatial map-ping of creative industries by the dynamic component concerning new approaches to Exploratory Spatial Data Analysis. This com-ponent is based on unbalanced panel dataset by using the differential local Moran’s I. The results indicate a dynamic development of design and advertising enterprises at the municipal level in the Czech Repub-lic, with options for internationalization of market, uniqueness of products and continual digitalization. On the contrary, subsector of architecture was identified as stagnant in terms of development, in relation to demand for these services that are affected by limited national real estate market, continual concentration of developers. Furthermore, the results revealed links between their spatial diffu-sion with process of residential suburbanization and strengthening of existing centres through the agglomeration and urbanization economies. Thus, those specifics underline a call for appropriate smart specialization policies along with policies concerning creative class retention in regional centres and rural areas.